2020
DOI: 10.1158/0008-5472.can-19-2060
|View full text |Cite
|
Sign up to set email alerts
|

A Feedback Circuitry between Polycomb Signaling and Fructose-1, 6-Bisphosphatase Enables Hepatic and Renal Tumorigenesis

Abstract: Suppression of gluconeogenesis elevates glycolysis and is commonly observed in tumors derived from gluconeogenic tissues including liver and kidney, yet the definitive regulatory mechanism remains elusive. Here, we screened an array of transcription regulators and identified the enhancer of zeste homolog 2 (EZH2) as a key factor that inhibits gluconeogenesis in cancer cells. Specifically, EZH2 repressed the expression of a rate-limiting gluconeogenic enzyme fructose-1, 6-bisphosphatase 1 (FBP1) and promoted tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
(57 reference statements)
0
24
0
Order By: Relevance
“…Enhancement of FBP1 expression could be exploited as a putative therapeutic approach to inhibit glycolysis and reverse the Warburg phenotype in cancer cells. In this study, the authors identified EZH2 as a negative regulator of FBP1 expression in liver and kidney cancer cells (1). A direct inhibitory effect of EZH2 on FBP1 expression via H3K27me3 in FBP1 promoter regions was shown in malignant liver and kidney epithelial cells using gain-of-function and loss-of-function experiments (1).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Enhancement of FBP1 expression could be exploited as a putative therapeutic approach to inhibit glycolysis and reverse the Warburg phenotype in cancer cells. In this study, the authors identified EZH2 as a negative regulator of FBP1 expression in liver and kidney cancer cells (1). A direct inhibitory effect of EZH2 on FBP1 expression via H3K27me3 in FBP1 promoter regions was shown in malignant liver and kidney epithelial cells using gain-of-function and loss-of-function experiments (1).…”
mentioning
confidence: 95%
“…3,4). This article adds an important piece to the puzzle of deregulated cancer cell metabolism by dissecting a doublenegative feedback mechanism, leading to suppressed FBP1 expression in gluconeogenic tissues and enhancement of tumor growth (1).…”
mentioning
confidence: 99%
“…The first loop is FBP1 and enhancer of zeste homolog 2 (EZH2): EZH2 can inhibit FBP1 and FBP1 physically competed for EZH2 binding in turn. 15 The second loop is FBP1 and polycomb repressive complex 2 (PRC2). PCR2 can downregulate FBP1, and conversely, FBP1 can interfere with PCR2 functions.…”
Section: Treatments For Aerobic Glycolysismentioning
confidence: 99%
“…Nevertheless, the decrease of PCK1 and FBP1 expression in HCC compared to normal liver tissue lead to the suppression of gluconeogenesis and elevation of glycolysis. 15,16 As an emerging hallmark of tumors, studies regarding glucose metabolism reprogramming used to focus on glycolysis. However, the correlation between gluconeogenesis and tumors is rarely reported but may provide insight for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Fructose-1, 6-biphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis, and functions as a negative regulator of the Warburg effect 1 . As a tumor suppressor, FBP1 plays a crucial role in tumor progression in multiple cancers 2 . Low expression of FBP1 is associated with tumorigenesis and poor prognosis in patients with breast, kidney, colon, pancreas, lung, stomach and liver cancers 3 - 8 .…”
Section: Introductionmentioning
confidence: 99%